The Influence of Crisis on Small Enterprise Growth - Gorzelany-Dziadkowiec, Magdalena; Kozień, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article identifies and analyses the reasons crisis befalls enterprises, and their influence on enterprise survival and growth. Analyses were performed based on small and micro- enterprises, both important components of an economy. The investigations were performed for three firms and were done in two stages. The small businesses surveyed may be found in the first two phases of L. E. Greiner's model. Emerging crises are overcome by delegating power and cooperating. In the second stage of the research, the owners answered a questionnaire concerning the cause of crisis and its influence on enterprise growth.